Identification and determination of genetic diversity in simian malaria parasites among wild long-tailed monkey populations from various regions of Peninsular Malaysia - Khajeaian, Parastoo (2015)
Malaria still remains a major cause of mankind death globally in spite of a century of research. It is clear that, understanding and accurate measurement of malaria incidence as one of the most critical tropical diseases have significant role to control and prevent this lethal infection.Since the probability of P. knowlesizoonotic transmission to humanswas proven, the necessity of study on simian malaria parasites isincreasingly obvious. Simian malaria parasites are readily infectious to long-tailed (Macaca facsicularis) and pigtailed (Macaca nemestrina) monkeys. The chance of this pathogenic species switching to humans as their desired host is not ignorable due to theincrease of human populations in recent years, as well asecological alterations which are causedby pollution or deforestation. In fact macaques are preferred host for Anopheles mosquitoes but human may change this situation by alteration on the natural habitat of macaques and mosquitoes. In this study, the distribution of five Plasmodium species namely: P. knowlesi, P. inui, P. cynomolgi, P. fieldi and P. coatneyiamong the wild populations of M. fascicularisin six states in Peninsular Malaysia were determined using highly specific (nested-PCR) assays. The advantage of this method lies in its ability to detect very low numbers of parasites. Monkey blood samples provided by the Department of Wild Life and National Parks Malaysia (PERHILITAN) were collected on Flinders Technical Association cards (FTA cards). FTA cardsare strongly recommended for collecting fluid samples for epidemiological studies particularly when sampling is being done in areas far from the main laboratory or during a long sampling trip. The prevalence of these five simian Plasmodiumspecieswas determined in 13 different locations of Peninsular Malaysia.Geographic distribution of the collected samples provided by PERHILITAN ranged from Northwest [Penang (island), Penang (mainland) and Jerejak Island], West (Selangor, Perak), Southwest (Negeri Sembilan), East (Pahang) and Northeastern (Kelantan) of Peninsular Malaysia. DNA was extracted from the blood spots on FTA Cards. All five simian Plasmodium species were successfully detected using nested PCR assay. Among the five species, P. knowlesi had the highest prevalence (34.3%), followed by P. inui (33.2%),P. cynomolgi (27.9%), P. fieldi (27.6%) and P. coatneyi(16.6%). Co-infections of macaques with multiple species of Plasmodium parasites were also observed. Kelantan had the highest prevalencerate among the states for all five simian malaria species. The incidence rate of three Plasmodiums pecies which are P. inui, P. fieldiand P. knowlesi were higher than 50% among the samples obtained from this state. Twenty positive DNA samples with single infection of P. knowlesi(12 samples) andP.cynomolgi (8 samples)as well as 20 uninfected monkey DNA samples were chosen to investigate the genetic diversity of these parasites using 26 different ISSR (inter simple sequence repeat)markers. A total of 103 ISSR loci for infected samples and 95 for uninfected samples were generated. The analyses of the infected and uninfected samples using ISSR markers confirmed the efficiency of both the markers and the clustering methods. By these methods, the samples not only were separated according to their geographical distribution, but the samples were grouped into two distinct clusters according to the species of the malaria parasite. Overall, this study shows the importance of research aboutmalaria parasite species which are infectious toM. fascicularis and the necessity of preventive and control plans to decrease the chance of host- switchoccurrence.Thisstudy also provides information for further investigations to design and develop diagnostic microsatellite markers for the macaques in the future.